Distorsi dan Politisasi Hadis dalam Politik Indonesia: Studi atas Gerakan 212 - Jannah, Safri Nur; Nanda Ahmad Basuki (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2024)
This study examines how hadiths were misinterpreted and politicized within the realm of practical politics in Indonesia, with a particular focus on the 212 Movement and the 2017 Jakarta gubernatorial election. It seeks to analyze different ways hadiths were utilized for political purposes during the 212 Movement and how this influenced Ahok’s electability. Using a literature review approach, the research incorporates Domke and Coe’s theory of religious politicization and Vedi R. Hadiz’s concept of Islamic populism to understand how religious texts—especially hadiths—were employed to rally public support. The study identifies four key methods of hadith politicization: altering context, misinterpreting meanings, selectively citing supportive hadiths, and using them as tools for mass mobilization. While the politicization of hadiths was not the sole factor behind Ahok’s declining electability, it played a contextual role in shaping public opinion—evident through memes, posters, banners, digital content, and social media hashtags. The research also underscores the influence of digital news outlets and mainstream media in framing the narrative around the 212 Movement and swaying public sentiment. In conclusion, the politicization of hadiths significantly affected Indonesia’s political landscape, especially during the events surrounding the 2017 Jakarta election.